Standardization of herbal medicines – an overview - Bhairam, Monika; Roy, Amit; Bahadur, Sanjib; Banafar, Alisha; Turkane, Dhanushram (Journal of Applied Pharmaceutical Research, 2013)
In the few decades, there has been exponentional growth in the field of herbal medicines. Most of the traditional systems of medicine are effective due to lack of standardization. So there is a need to develop a standardization technique. Standardization of herbal formulation is essential in order to assess the quality, purity, safety and efficacy of the drug. There is increasing awareness and general acceptability of the use herbal drugs in today’s medical practice. The world population depends on herbal medicines and product for healthy living. This rise in the use of herbal product has also given rise to various forms of adulteration of the products, which leading to consumers’ and manufacturers’ disappointment and in some instances fatal consequences. The challenge is innumerable and enormous, to fulfill the need of global herbal market. The standardization of this formulations like the organoleptic characters, physical properties, the various physic-chemical properties such as moisture content, ash values, extractive values need to be carried out along with Thin layer chromatography and heavy metal content study should also carried out to ascertain the quality, purity and safety of this herbal formulation.